Contextual-based Interactive Economic Learning Media Effectively used in Science and Social Learning of Fifth Grade Elementary School - Cahyani, Komang Nanda; Agustika, Gusti Ngurah Sastra (Journal for Lesson and Learning Studies, 2024)
At this time, educators are still more dominant in using books in science and science learning, which makes students lazy to read books. Educators should be able to develop learning media to support student learning. This research aims to develop interactive learning media based on a contextual approach that is tailored to student needs which can help teachers in implementing learning. The model used in developing this media is the ADDIE model. Based on the research that has been carried out, the results obtained are interactive learning media that is suitable and effective for use in learning. The interactive learning media based on the contextual approach that was developed was declared feasible and effectively applied in the learning process. The results of the effectiveness test calculation based on the results of the univariate t-test obtained a tcount of 13,945 which was then compared with the ttable value at a significance level of 5% with dk = 27 which was 2.05. The results show that t-count > t-table (13,945 > 2.05), so H0 is rejected and Ha is accepted. The effectiveness of using interactive learning media can also be seen from the increase in the average science knowledge competency of students as measured through pretest and posttest. The average pretest score was 58.9 and the average posttest score was 92.6. Thus, it can be concluded that interactive learning media for economic material can be applied in learning science content for fifth grade elementary school.